Arab Saudi dan Krisis Harga Minyak Tahun 2014-2016 [Saudi Arabia and the Oil Price Crisis of 2014-2016] - Wildan Faisol (Universitas Pelita Harapan, 2018)
This article explains the Saudi Arabian oil crisis of 2014-2016. In 2014, the Organization of Petroleum Exporting Countries (OPEC) had been expected to cut production to stabilize the market and control the price of oil,but instead of reducing their own production, Saudi Arabia pushed OPEC to let the market control the price of of oil. This raised the question of why Saudi Arabia led the OPEC push to let the price decline. The purpose of this article is to understand the reasons behind Saudi Arabia’s efforts as prices plummeted fron 2014 until 2016. This paper explores Saudi Arabia as the de facto leader of OPEC using geopolitical purposes to influences the rest of OPEC and to weaken their opponents including Iran, Iraq and Russia.